(untitled) (Gadau Journal of Pure and Allied Sciences, 2025)
Superabsorbent hydrogels are being increasingly used as soil conditioners to enhance soil water retention, reduce the rate of irrigation and improve plant growth during drought. In the present work, superabsorbent hydrogel was prepared from cellulose based material with ethylenediamine as the crosslinking agent and evaluates it impact as water reservoir on maize growing in greenhouse. The cellulose isolated from rice husk, which has a basis to modify and obtain carboxymethylcellulose (CMC) using sodium hydroxide (NaOH) and monochloroacetic acid (MCA). The superabsorbent hydrogel was characterized by fourier transform infrared (FTIR) and x-ray diffraction (XRD). The percentage swelling attained by optimum conditions of time, power and amount of cross-linker required for the production of most desirable, stable and high water absorptivity were investigated, the optimum swelling capacity was found to be 1175%. The control pot (no superabsorbent hydrogels) revealed a significant difference in plant growth parameter and growth yield parameters compared to the pots treated with superabsorbent hydrogels. Increase in hydrogel dose significantly affects the growth and yield parameter of the maize. The optimum were recorded at 5grams for the superabsorbent hydrogels.